Expert and Lay Public Risk Preferences Regarding Plants with Novel Traits. (28th June 2016) - Lubieniechi, Simona; Hesseln, Hayley; Phillips, Peter; Smyth, Stuart
Abstract : The regulation, commercialization, and adoption of a new technology involve interplay of various stakeholders, including: scientists, researchers, and developers; businesspeople in management, finance, and marketing; government agents in policy and administration; and the general public. Outcomes of these processes are therefore a function of the risk preferences of various stakeholders. Our objective is to investigate the risk preferences regarding plants with novel traits among the lay public and regulatory professionals. We investigate how framing and perceptions affect risk preferences. In particular, we test how the concept of provenance, for example, whether technology is being provided by a public university versus a multinational corporation, might affect respondents' risk choices. We conducted a modified "Asian disease" experiment to test for Tversky and Kahneman's (1981) prospect theory, adapting the choice task to the context of new technology in agriculture. We found that framing manipulations yielded different results for both experts and laypersons: positive framing induced risk aversion more so than negative framing induced risk seeking. While framing has a strong impact on all respondents, the provenance effect is weak and inconsistent across results.